Patient consent in the modern era: Novel tools and practical considerations in urology - Elisha Ogbodo; Ali Talyshinskii; Christian Arvei Moen; Esteban Emiliani; Bhaskar Kumar Somani; Lazaros Tzelves; Christian Beisland; Patrick Juliebø-Jones (Current Urology)
Abstract. Informed consent is a cornerstone of ethically acceptable surgical interventions. Traditional methods primarily rely on verbal explanations by clinicians and, at times, the use of supplementary resources such as information leaflets. In the modern era, novel tools have emerged to facilitate and enhance the consent process. Examples include multimedia, 3D models, virtual and augmented reality, quick response codes, and artificial intelligence technologies such as large language models. This narrative review provides an overview of these aids, discussing their potential advantages and limitations. In addition, the influence of social media on the consent process is explored.